1992
DOI: 10.3758/bf03211630
|View full text |Cite
|
Sign up to set email alerts
|

Single-parameter power law psychophysics of auditory numerosity and the psychological moment hypothesis

Abstract: In the present study, numerosity estimation was investigated. A two-parameter Stevens power law analysis was performed on a total of 944 subjects in six experiments. Two pulse ranges (2-17 or 17-253 pulses) and six pulse rates (either constant or randomly varied within trial blocks) were used, variously, in an unsuccessful attempt to find evidence for a psychological moment, under the supposition that the exponent (or, possibly, the measure constant) would become smaller as increasing numbers of pulses fell wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 107 publications
(132 reference statements)
0
6
0
Order By: Relevance
“…Raninen, Franssila, & Rova mo, 1991), temporal order judge ments (Rutschm ann, 1973;Ulrich, 1987), two-flash fusion (Boynton, 1972), the detection of simultaneity (Allan, 1975;Baron, 1971), duration discrimination (Kristofferson, 1977(Kristofferson, , 1980, m etacontrast (U ttal, 1971) and temporal num erosity (W hite, 1963). For the auditory modality, temporal resolution has been investigated for temporal order judgem ents (Corso, 1980 ;Hirsh & Sherrick, 1961), temporal num erosity (Cheatnam & W hite, 1954;Robinson, 1992), two-click fusion (Boynton , 1972) and duration discrimination (Rousseau, Poirier, & Lem yre, 1983).…”
Section: A D E F In I T I O N O F T E M P O R a L P R O C E S S I N Gmentioning
confidence: 99%
“…Raninen, Franssila, & Rova mo, 1991), temporal order judge ments (Rutschm ann, 1973;Ulrich, 1987), two-flash fusion (Boynton, 1972), the detection of simultaneity (Allan, 1975;Baron, 1971), duration discrimination (Kristofferson, 1977(Kristofferson, , 1980, m etacontrast (U ttal, 1971) and temporal num erosity (W hite, 1963). For the auditory modality, temporal resolution has been investigated for temporal order judgem ents (Corso, 1980 ;Hirsh & Sherrick, 1961), temporal num erosity (Cheatnam & W hite, 1954;Robinson, 1992), two-click fusion (Boynton , 1972) and duration discrimination (Rousseau, Poirier, & Lem yre, 1983).…”
Section: A D E F In I T I O N O F T E M P O R a L P R O C E S S I N Gmentioning
confidence: 99%
“…Garner (1951), too, concluded from a control experiment that randomization of IOIs made little difference. Other authors, however, have found that experimental design does matter, especially at very fast presentation rates (John, 1972;Robinson, 1992). The training of participants also plays a role.…”
mentioning
confidence: 98%
“…Interestingly, they obtained a similar estimate of subjective rate for auditory and visual stimuli (Cheatham & White, 1952;Forsyth & Chapanis, 1958;White, 1963;White & Cheatham, 1959;White, Cheatham, & Armington, 1953), and Cheatham and White (1954) thought that this amodal limit was related to the alpha rhythm of brain waves. However, John (1972) expressed reservations about the constancy of subjective rate in view of the effect of experimental design factors, and both he and others (Pollack, 1968;Robinson, 1992) have pointed out that there is an inevitable confound between numerosity perception and perception of sequence duration, especially at fast rates at which numerosity can only be estimated. Perhaps as a consequence of this realization, there has been little recent research on auditory numerosity perception.…”
mentioning
confidence: 99%
“…A number of researchers have examined the relation between the coefficient (or its logarithm) and the exponent for different experimental conditions or for individual subjects (e.g., Baird, Kreindler, & Jones, 1971;Gescheider & Hughson, 1991;Kowal, 1987;Robinson, 1992;Stevens, 1974), and most have found the coefficient to be negatively related to the exponent. From the point of view of the coefficient as an indication of the size of the response, the negative relation would suggest that subjects or experimental conditions that produce greater responses tend to yield lower exponents.…”
mentioning
confidence: 99%
“…Rule, Department of Psychology, University of Alberta, Edmonton, AB, Canada, T6G 2E9. tin, 1983;Gescheider & Hughson, 1991;Kowal, 1987;Robinson, 1992). Some of these studies were designed to show that the unit of subjects' responses is stable with respect to changes in experimental procedure or with the same experimental procedure on different occasions.…”
mentioning
confidence: 99%